Development of Smart Art Bench Design Equipped with AI n-type Solar Power - Tae-Won Oh (International Journal of Advanced Culture Technology(IJACT), 2025)
The integration of sustainable energy solutions and smart technologies in urban environments is becoming increasingly important. In particular, there is a growing demand for facilities that are both functional and aesthetically pleasing in public spaces. Existing solar technologies have had difficulty producing energy without compromising the urban landscape due to efficiency and design constraints. This paper focuses on this very point and aims to develop a smart art bench design that combines AI technology and high-efficiency n-type solar power. The goal is to design a bench that naturally blends into urban spaces while producing energy and providing various smart functions. In the design process, we first considered an aesthetic form and layout suitable for the urban environment, then studied the application of the latest n-type solar panels to increase energy production efficiency, and utilized AI algorithms for optimal panel layout and energy management. In addition, we explored ways to integrate smart functions (e.g. USB charging, Wi-Fi hotspot, environmental information provision, etc.) into the design to increase user convenience. The smart art bench design developed in this way can serve as a distributed energy source that produces energy for the city itself, provide convenient smart services to citizens, and contribute to improving the city’s appearance. Furthermore, it is expected to become a model case for implementing a sustainable smart city. The smart art bench design developed in this way will serve as a decentralized energy source that produces the city's energy by itself, provide convenient smart services to citizens, and contribute to improving the city's aesthetics. Furthermore, it is expected to serve as a best practice in implementing a sustainable smart city.